DNA polymerases drive DNA sequencing-by-synthesis technologies: both past and present - Chen, Cheng-Yao (Frontiers in Microbiology, 2014)
Next-generation sequencing (NGS) technologies have revolutionized modern biological and biomedical research. The engines responsible for this innovation are DNA polymerases; they catalyze the biochemical reaction for deriving template sequence information. In fact, DNA polymerase has been a cornerstone of DNA sequencing from the very beginning. E. coli DNA polymerase I proteolytic (Klenow) fragment was originally utilized in Sanger's dideoxy chain terminating DNA sequencing chemistry. From these humble beginnings followed an explosion of organism-specific, genome sequence information accessible via public database. Family A/B DNA polymerases from mesophilic/thermophilic bacteria/archaea were modified and tested in today's standard capillary electrophoresis (CE) and NGS sequencing platforms. These enzymes were selected for their efficient incorporation of bulky dye-terminator and reversible dye-terminator nucleotides respectively. Third generation, real-time single molecule sequencing platform requires slightly different enzyme properties. Enterobacterial phage ⱷ29 DNA polymerase copies long stretches of DNA and possesses a unique capability to efficiently incorporate terminal phosphate-labeled nucleoside polyphosphates. Furthermore, ⱷ29 enzyme has also been utilized in emerging DNA sequencing technologies including nanopore-, and protein-transistor-based sequencing. DNA polymerase is, and will continue to be, a crucial component of sequencing technologies.